2019
DOI: 10.1097/coh.0000000000000579
|View full text |Cite
|
Sign up to set email alerts
|

Reaching the second 90

Abstract: Purpose of reviewWe present recent literature describing interventions for linkage to HIV care in the era of Universal Test and Treat (UTT) policies. We also provide information for ongoing studies of linkage to care strategies registered with ClinicalTrials.gov.Recent findingsDifferentiated service delivery for linkage to care involves implementing strategies that simplify and adapt HIV services to better serve individual needs and reduce unnecessary burdens on the health system. Recent strategies have focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Some of these solutions included support for transport and/or escort to health facilities to facilitate linkage, as well as provision of other supportive services, such as psychosocial and education support. This is consistent with other studies that have found these interventions to be effective for improving LTC [17][18][19]. It is likely that involving CBOs in linkage to care also reduced the level of mistrust and reservations observed in communities, whenever community health activities including unfamiliar persons, such as NAIIS staff, enter communities.…”
Section: Plos Onesupporting
confidence: 89%
“…Some of these solutions included support for transport and/or escort to health facilities to facilitate linkage, as well as provision of other supportive services, such as psychosocial and education support. This is consistent with other studies that have found these interventions to be effective for improving LTC [17][18][19]. It is likely that involving CBOs in linkage to care also reduced the level of mistrust and reservations observed in communities, whenever community health activities including unfamiliar persons, such as NAIIS staff, enter communities.…”
Section: Plos Onesupporting
confidence: 89%
“…Patients who did not disclose their known HIV-positive status may have been reluctant to do so due to HIV related stigma which is prevalent. 20 , 21 In our study, of the 206 positive cases, 152 (73.8%) known infected patients had not disclosed their status. Fear of discrimination that can affect the patient wellbeing is likely one of the reasons some of the patients fail to disclose their HIV status.…”
Section: Discussionmentioning
confidence: 52%
“…This is an important finding as it has been proven that failures in linkage to care are associated with lower levels of viral suppression and greater likelihood of viral resistance. 21 - 23 …”
Section: Discussionmentioning
confidence: 99%
“…Without barrier‐free access to ART, achieving and maintaining an undetectable viral load cannot become a reality for the majority of people living with HIV. It is therefore essential to address the structural and societal barriers that exist across HIV care to increase uptake and maintenance of ART [11]. In addition, there is a requirement for differentiated and integrated models of care to ensure that the unique needs of key populations are addressed [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore essential to address the structural and societal barriers that exist across HIV care to increase uptake and maintenance of ART [11]. In addition, there is a requirement for differentiated and integrated models of care to ensure that the unique needs of key populations are addressed [11]. A person‐centred care model with a focus on retention and re‐engagement will help address barriers to care [11] and enable the updated Joint United Nations Programme on HIV/AIDS (UNAIDS) 95‐95‐95 targets and the WHO's new 2022–2030 global health sector strategy for HIV to be achieved [12, 13].…”
Section: Discussionmentioning
confidence: 99%